Integrative multi-omics analysis and machine learning reveal the unique role of ASCC3 in combination with various immune-related genes in rectal adenocarcinoma - Chuang Miao; Fei Qian (Frontiers in Genetics)
BackgroundThe Activating Signal Cointegrator 1 (ASC-1) complex is a tetrameric complex composed of Thyroid Hormone Receptor Interactor 4 (TRIP4), Activating Signal Cointegrator 1 (ASCC1), Activating Signal Cointegrator 2 (ASCC2), and Activating Signal Cointegrator 3 (ASCC3). As the core subunit of the ASC-1 complex, ASCC3 is involved in DNA damage repair. However, the exact role of ASCC3 in digestive system cancers, particularly in rectal adenocarcinoma (READ), remains unclear.MethodsWe utilized data from The Cancer Genome Atlas (TCGA) and GEO to investigate the prognostic value of the four subunits, with a focus on ASCC3, in pan-cancers including rectal adenocarcinoma. Additionally, we explored the regulatory mechanisms of ASCC3 and its association with tumor immunity in rectal adenocarcinoma using TIMER, IMMPORT, DAVID databases, and CIBERSORT analysis. Prognostic models were constructed using ssGSEA analysis and various machine learning algorithms. We explored the signaling pathways regulated by ASCC3 using the CancerSEA and TCPA databases. Furthermore, mutations of ASCC3 in pan-cancer were investigated using the PFAM and CbioPortal databases. Finally, we performed interaction network analysis of ASCC3 using STRING, ComPPI, and BioGRID databases.ResultsASCC3 is a specific protective factor for rectal adenocarcinoma across various cancer types, particularly in digestive system cancers, and can synergize with several immune-related genes, including JAK1, NFKB1, SEMA5A, NR2C2, CNTF, and CREB1, to influence patient prognosis. Furthermore, ASCC3 may regulate tumor immunity by affecting T cell function.ConclusionASCC3 can serve as an independent prognostic factor for READ and can synergize with various immune-related genes to influence patient prognosis.